THE EFFECT OF LOCAL VIBRATION IN CROSS COUNTRY SKIING (DIAGONAL STRIDE) - Ciekurs, Kalvis; Krauksts, Viesturs; Krauksta, Daina; Grants, Juris; Alekrinskis, Aleksandras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Local vibration (LV) is innovation as a part of training method that helps athletes to regain the power and get ready for next training faster. There are many discussions about how to increase moving speed in cross-country skiing. Many scientists research the possibilities of increasing moving speed in this sport. Cycle duration in different moving strides along different course terrains is stated, including even stride cycle duration separately for the leg and arm movements. It is proved by many studies that moving speed depends on stride cycle duration. A pilot study was carried out. Two LASE specialization students participated in the study. The following methods were used in the study: videoanalysis, LV manipulations, the stating experiment and mathematical statistics. The videoanalysis was made with Panasonic digital video camera (50 Hz), and the obtained data were processed using a videoanalysis program. LV manipulations were done to the muscles m. Erector spinae, m. Latisimus dorsi, m. Deltoideus, m. Trapecius and m. Triceps Brachi using 100 Hz frequency and different pressure on the muscles. The total LV application time was 10 min. with 30 min. relaxation. The obtained data were processed using mathematical statistics. The results: having stated the result difference before LV and after it. The results testify significant improvement of diagonal stride results, what is showed by the difference of the mean results. The results: having stated the result difference before LV and after it, it was stated that the mean moving speed of both students (S1 and S2) in the cycle before LV was 4.14m/s (S1) and 3.97m/s (S2), but after the application of LV the mean moving speed in a cycle was 4.51m/s (S1) and 4.25m/s (S2), thus the difference of the means was 0.37m/s (S1) and 0.28m/s (S2).